Diabetes Mellitus in Patients Presenting with Cardiovascular Events: Descriptive Analysis from a Tertiary Heart Hospital Over a 22-year Period - El-Menyar, Ayman; Al-Thani, Hassan; Mekkodathil, Ahammed; Mohammed, Shaban; Singh, Rajvir; AlBinAli, Hajar; Suwaidi, Jassim A. (Current Vascular Pharmacology, 2015)
Background: Diabetes mellitus (DM) remains a health care challenge worldwide. We evaluated the trends and outcome of DM in patients presenting with cardiovascular diseases (CVD) over a 22-year period in Qatar. Methods and Results: A retrospective analysis was performed between 1991 and 2012, including 48,803 patients admitted to the tertiary Heart Hospital (HH). The average CVD hospitalization rate was 37 admissions per 10,000 people, of which, 2 out of 5 patients had DM. Diabetic males were 6 years younger than females. DM was more prevalent in Arabs (68 vs. 32%), but its burden showed a decreasing trend over time compared with South Asians. More diabetics presented with ST-elevation myocardial infarction (47.5 vs. 22.7%), which tended to occur 8 years earlier compared with heart failure. Over the study period, beta-blocker use increased substantially (from 10 to 71%). However, angiotensin converting enzyme inhibitors/angiotensin receptor blockers (ACEI/ARBs) were underutilized (from 30 to 56%). There were 4.4 deaths per 100 CVD admissions, which is equivalent to 97 deaths per year. Of this, 52% had DM (2.3 deaths per 100 CVD admissions). The overall case fatality rate (CFR) of DM was 5.6%. Diabetic Asian patients died 9 years earlier than diabetic Arabs at the HH. Multivariate regression analysis revealed that predictors of mortality in DM patients in the HH included lack of beta-blocker use (OR 4.35; 95% CI: 0.20 – 0.27), lack of ACEI/ARBs use (OR 3.58; 95% CI: 0.23 – 0.32), myocardial infarction (OR 3.20; 95% CI: 2.77 – 3.68), lack of aspirin use (OR 2.56; 95% CI: 0.34 – 0.45), congestive heart failure (OR 1.75; 95% CI: 1.50 – 2.04) and age (OR 1.03; 95% CI: 1.02 – 1.04) (P=0.001 for all). Conclusion: DM remains a healthcare challenge in Qatar. Although the admission rate of diabetic patients is increasing at the HH, the mortality rate is decreasing. The use of evidence-based medication is still far from the guideline recommendation; however, it has substantially improved. The lack of evidence-based CVD medications in diabetic patients was associated with an increased mortality up to 4-fold in the HH. Moreover, there is a need to enhance public awareness regarding CVD risk factors and DM through education programs for the adoption of healthier lifestyles and nutrition. Great efforts are needed for more efficient primary and secondary prevention strategies in diabetic patients.
Keywords: Qatar